Hydrogeological and Environmental Investigations in Karst Systems - Andreo, Bartolomé (Springer, 2015)
The editors of the book would like to thank the members of the Organizing and the Scientific Committees and the authors and reviewers of the manuscripts of the Fifth International Symposium on Karst Aquifers (ISKA5) for their contributions and collaboration. Members of the Scientific Committee composed of 41 international specialists from various karst domains, along with members of the Organizing Committee are listed accordingly. All the manuscripts were reviewed and only those that met the required criteria and quality were accepted...